PENGETAHUAN DAN SIKAP SISWA TERHADAP BENCANA GUNUNG BERAPI - Erly Mauvizar; Ani Darliani; Hayati Hayati; Wirda Wirda (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Calling upon the potential for disasters in Indonesia, disaster education in early childhood education seems very crucial. Disaster education is an effort to create good knowledge, good conditions, and a strong attitude in dealing with disasters. Disaster education can be carried out at all levels of education, both formal and informal. The purpose of this study was to determine knowledge and attitudes towards the risk of volcanic disaster in Aceh Besar SAIBAS students. The method used in this research is a descriptive statistical approach with a quasi-experimental research design. The quasi-experiment used in this study is Quasi-Experiment: One-Group Pretest-Posttest. The research was conducted at the Bukit Pedas Islamic Kindergarten (SAIBAS) Aceh The sampling procedure employed in this study involved the utilization of purposive sampling, specifically targeting a cohort of 30 students. The data collection instruments encompassed Likert attitude scales, interviews, and test results. Test analysis techniques were employed for the subsequent data analysis. The findings of the intervention revealed a notable enhancement in both knowledge and attitudes, registering an initial increase of 53 and subsequently escalating to 87. Moreover, the participants demonstrated an 85 capacity in disaster preparedness, underscoring their adeptness in comprehending the risks associated with volcanic activity. This discernible improvement in student capabilities underscores a heightened awareness and understanding of volcanic hazards. There are changes in attitude and knowledge after gaining knowledge about disaster mitigation